Financial Literacy and Behavioral Bias Towards Consumptive Behavior: Evidence from Bandung, Indonesia - Astrie Krisnawati; PUTRI SYA’ADATUL FADILA; PUTRI FARISKA; NORA AMELDA RIZAL (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Bandung is a city with a notably elevated per capita spending rate. It denotes a considerable degree of consumptive behavior, which can be attributed to various factors. This research delves into the impact of financial literacy and behavioral bias on consumptive behavior within the productive-age population of Bandung. Employing a quantitative methodology, the study gathered data by administering surveys to 400 participants using the Slovin formula and purposive sampling methods. The data analysis was conducted through multiple linear regression. It reveals that financial literacy and behavioral bias possess significant partial and simultaneous influences on consumptive behavior. The study's results suggest that the Financial Services Authority (OJK) needs to enhance financial education initiatives among the productive-age population. Its implications for future research involve supplementary independent variables, such as framing bias and demographic factors.